Proses Penyelenggaraan Event Musyawarah Nasional Organisasi Profesi Pejabat Pengawas Lingkungan Hidup Tahun 2023 oleh PT Genesia Dwi Mitra - Ramadhona, Astri Amalia; Muhammad Iqbal Katik Rajoendah (Lembaga Pengembangan Kinerja Dosen, 2024)
Environmental pollution and damage are increasing so this situation can disrupt human life. To overcome this problem, comprehensive efforts are needed in the form of strict and sustainable law enforcement by Pejabat Fungsional Pengawas Lingkungan Hidup (PPLH). One of the things PPLH did to form the professional organization was to hold the first Organisasi Profesi Pejabat Pengawas Lingkungan Hidup National Conference in 2023 online and offline on Wednesday, December 6, 2023, which appointed PT Genesia Dwi Mitra as the event organizer. This research aims to understand the process of organizing the 2023 Organisasi Profesi Pejabat Pengawas Lingkungan Hidup National Conference. The author applies a qualitative method by collecting data through participatory observation, documentation, and literature study. The findings show that PT Genesia Dwi Mitra has carried out the preparation and implementation stages of the event, referring to the terms of reference (ToR) provided by the client.